Spatial and temporal changes in bomb radiocarbon in the northern Indian Ocean. (October 2021) - Raj, Harsh; Bhushan, Ravi
Abstract: For improved understanding of ocean circulation in the northern Indian Ocean region, long term continuous record of radiocarbon measurement is required. Limited radiocarbon records from the region demands investigations of natural archives. Coral core records along with some literature data were analysed to study the temporal changes in 14 C values over the northern Indian Ocean. The major fraction of the bomb radiocarbon appears to have transferred in to the ocean, as recent records from the surface seawater Δ 14 C values show comparable or even higher than the atmospheric Δ 14 C values. The northern Andaman region showed higher Δ 14 C decline rate between 1978 and 2014 compared to the southern Bay of Bengal and the Lakshadweep region. The comparable southern Bay of Bengal and the Lakshadweep Δ 14 C values could be due to transfer of Arabian Sea waters to the southern Bay of Bengal. The southern Andaman region shows lower Δ 14 C values compared to the northern Andaman region, suggesting the influence of 14 C depleted waters in the region. Highlights: Comparison of temporal changes in surface Δ 14 C value of the northern Indian Ocean. Northern Andaman shows enriched Δ 14 C value compared to the atmosphere. Δ 14 C decline rate in the Southern Bay of Bengal is lower than the Northern Andaman. Lakshadweep and Southern Bay of Bengal show comparable surface Δ 14 C values.